Adult-Adult and Adult-Child/Adolescent Online Sexual Interactions: An Exploratory Self-Report Study on the Role of Situational Factors - Emilia Bergen; Anna Ahto; Anja Schulz; Roland Imhoff; Jan Antfolk; Petya Schuhmann; Katarina Alanko; Pekka Santtila; Patrick Jern (Tayler & Francis, 2022)
Alcohol intoxication, sexual arousal, and negative emotional states have been found to precede certain sexual behaviors. Using data from an online self-report survey distributed to adults (N = 717; 423 men and 304 women), we compared adults with adult online sexual interactions (n = 640; 89.3%) to adults with interactions with a child or an adolescent (n = 77; 10.7%) on how much they reported being affected by the following factors surrounding the time of the interactions: alcohol intoxication, sexual arousal, sadness, boredom, stress, and shame. We found that those with a child or adolescent contact reported higher sexual arousal and more shame before the interaction, compared with those with an adult contact. In addition, the levels of negative emotional states varied when levels before the interactions were compared with levels after the interactions, suggesting that engaging in online sexual interactions alleviated negative emotional states, at least temporarily. The alleviatory effects, however, were accompanied by higher levels of shame after the interactions. Overall, adults that engage in online sexual interactions have remarkably similar perceptions of the situation surrounding these activities, independent of the age of their online contacts. Limitations of the study are discussed.